2012
DOI: 10.1021/pr300173c
|View full text |Cite
|
Sign up to set email alerts
|

Combined Metabonomic and Quantitative Real-Time PCR Analyses Reveal Systems Metabolic Changes in Jurkat T-Cells Treated with HIV-1 Tat Protein

Abstract: HIV-1 Tat protein is released by infected cells and can affect bystander uninfected T cells and induce numerous biological responses which contribute to its pathogenesis. To elucidate the complex pathogenic mechanism, we conducted a comprehensive investigation on Tat protein-related extracellular and intracellular metabolic changes in Jurkat T-cells using combined gas chromatography-mass spectrometry (GC-MS), reversed-phase liquid chromatography-mass spectrometry (RPLC-MS) and a hydrophilic interaction liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 64 publications
1
18
1
Order By: Relevance
“…Interestingly, much of the proteomic data has been corroborated by previous publications for on the ETC [1012] and glycolyic pathway [5557] albeit in alternative cell types or animal models. Together these data suggest the HIV-1 viral proteins produce chronically dysfunctional mitochondria, and these mitochondrial alterations can contribute to the HAND functional pathology.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Interestingly, much of the proteomic data has been corroborated by previous publications for on the ETC [1012] and glycolyic pathway [5557] albeit in alternative cell types or animal models. Together these data suggest the HIV-1 viral proteins produce chronically dysfunctional mitochondria, and these mitochondrial alterations can contribute to the HAND functional pathology.…”
Section: Discussionmentioning
confidence: 55%
“…Previous work on glycolysis levels in cells exposed to HIV-1 viral proteins have produced varied results. In a variety of cells, exposure to certain HIV-1 viral proteins in vitro or HIV-1 virus in vivo results in increased glycolysis [5557]. Conversely, isolates of blood from HIV-1 infected individual have also demonstrated decreased glycolysis [58].…”
Section: Discussionmentioning
confidence: 99%
“…However, five pivotal intermediates of the citrate cycle: citric acid (FC = −0.44), cis-aconitic acid (FC = −0.28), 2-ketoglutaric acid (FC = −1.52), malic acid (FC = −0.38), and fumaric acid (FC = −0.31), were down-regulated in 3D4/2 cells infected with CSFV. This suggested that the citrate cycle might be inhibited by CSFV infection in 3D4/2 cells and this might be caused directly by a reduction of citrate synthesis, which is also found in T-cells treated with HIV-1 Tat protein (Liao et al, 2012). …”
Section: Discussionmentioning
confidence: 89%
“…The decline in malic acid and fumaric acid might be the result of regulation by downstream enzymes of 2-ketoglutaric acid or be attributed to excessive transformation of 2-ketoglutaric acid to proline. Similarly, reverse levels of intermediates in the citrate cycle are also discovered in cells infected by HIV-1 or human cytomegalovirus (HCMV) (Munger et al, 2006; Liao et al, 2012). However, five pivotal intermediates of the citrate cycle: citric acid (FC = −0.44), cis-aconitic acid (FC = −0.28), 2-ketoglutaric acid (FC = −1.52), malic acid (FC = −0.38), and fumaric acid (FC = −0.31), were down-regulated in 3D4/2 cells infected with CSFV.…”
Section: Discussionmentioning
confidence: 99%
“…with which metabolic responses to biological interventions or environmental factors are analyzed and modeled (4)(5)(6). Characterizing the metabolome via metabolic profiling provides insight into the state of the organism or substance at a particular moment (7).…”
mentioning
confidence: 99%